2020
DOI: 10.1126/sciimmunol.aba6087
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis of allergen-specific T cells in allergy and asthma

Abstract: CD4+ T helper (TH) cells and regulatory T (Treg) cells that respond to common allergens play an important role in driving and dampening airway inflammation in patients with asthma. Until recently, direct, unbiased molecular analysis of allergen-reactive TH and Treg cells has not been possible. To better understand the diversity of these T cell subsets in allergy and asthma, we analyzed the single-cell transcriptome of ~50,000 house dust mite (HDM) allergen–reactive TH cells and Treg cells from asthmatics with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 128 publications
8
123
1
Order By: Relevance
“…First, allergen-specific Th2 cells and their associated cytokines are clearly present in the bronchoalveolar lavage of asthmatic patients and mice with allergic eosinophilic asthma (Coquet et al, 2015;Robinson et al, 1992;Tibbitt et al, 2019). Then, circulating allergen-specific Th2 cells producing IL-4, IL-5, IL-13, and even IL-9 can be found in the blood of allergic asthmatic patients (Seumois et al, 2020). In addition, early studies performed in murine models of type 2-high asthma induced by the inhaled antigen ovalbumin (OVA) have demonstrated that the depletion of CD4 + T cells prevented asthma development and that, on the opposite side, the adoptive transfer of in vitro-polarized Th2 cells from mice with transgenic expression of an OVA peptide-specific T cell antigen receptor (TCR) lead to the induction of asthma features (Cohn et al, 1997).…”
Section: Th2 Cells and Their Cytokines Control Type 2-high Asthmamentioning
confidence: 99%
“…First, allergen-specific Th2 cells and their associated cytokines are clearly present in the bronchoalveolar lavage of asthmatic patients and mice with allergic eosinophilic asthma (Coquet et al, 2015;Robinson et al, 1992;Tibbitt et al, 2019). Then, circulating allergen-specific Th2 cells producing IL-4, IL-5, IL-13, and even IL-9 can be found in the blood of allergic asthmatic patients (Seumois et al, 2020). In addition, early studies performed in murine models of type 2-high asthma induced by the inhaled antigen ovalbumin (OVA) have demonstrated that the depletion of CD4 + T cells prevented asthma development and that, on the opposite side, the adoptive transfer of in vitro-polarized Th2 cells from mice with transgenic expression of an OVA peptide-specific T cell antigen receptor (TCR) lead to the induction of asthma features (Cohn et al, 1997).…”
Section: Th2 Cells and Their Cytokines Control Type 2-high Asthmamentioning
confidence: 99%
“…This analysis platform enables the assessment of gene expression in each individual cell which is superior to bulk analysis that often overlooks shifts in transcriptomic patterns by averaging the mRNA expression data [150]. In the field of allergy, scRNA-seq has already propelled knowledge of B cell class switching [151], B cell memory [46•], airway T cell metabolism [152], transcriptional differences between asthmatics with and without allergy [153], IgE responses [154], T cell clonotypes [155], and functional heterogeneity within allergen-specific T cell subset [156].…”
Section: Addressing the Unmet Needs And The Current Challenges In Biomentioning
confidence: 99%
“…There is no difference in the overall proportion of TRMs in the lungs of asthmatic versus healthy individuals, but scRNA-seq reveals that asthmatics have higher frequencies of lung-resident Th2 cells, displaying a pathogenic phenotype (Vieira Braga et al, 2019). HDM-specific CD4 + T cells also display a high degree of heterogeneity in allergic individuals, with the presence of functionally enhanced Th2 cells, including those expressing IL9, and type I IFN-responsive CD4 + T cells (Seumois et al, 2020), features replicated in the lungs of mice after repeated exposure to inhaled HDM (Tibbitt et al, 2019). Although data on the contribution of TRMs in humans is less abundant than for viral infection, murine models of HDM exposure have proven that allergen-specific TRMs are generated rapidly, remain resident in the lungs for the lifetime of the animal, and are necessary and sufficient to drive airway hyperreactivity (AHR) and type 2 inflammation (Bo snjak et al, 2019;Hondowicz et al, 2016;Turner et al, 2018).…”
Section: Review New Kids On the Block: Resident Adaptive Immune Cells Shape Re-encountersmentioning
confidence: 98%